Cognition does not automatically influence perception: Evidence from neural encoding of colors belonging to different categories - Jasna Martinovic; Alexey A. Delov; Jana Tomastikova; Joel T. Martin; Galina V. Paramei; Yulia A. Griber (Proceedings of the National Academy of Sciences, 2026)
The firmest evidence in favor of models that posit early high-level influences of cognition on perception comes from electroencephalography (EEG). Enhanced early, preattentive processing of light and dark blue feature changes compared to light and dark green changes was reported in Greek speakers, who have two basic terms for “blue” ( ghalazio/ble ). In the present three-experiment study, we systematically reevaluate this evidence and test an alternative model that the early difference waves in the human EEG instead mainly reflect contrast adaptation phenomena. We use the same classical oddball paradigm presenting alternating standards and deviants that systematically differ in color and/or luminance and chromatic contrast. We then calculate the visual mismatch negativity (vMMN), a putative index of preattentive feature change processing and predictive coding derived from EEG data, by subtracting the activity elicited by standards from that elicited by task-irrelevant deviants. Our experiments demonstrate the following: 1) vMMN is driven by contrast adaptation, being observable only in the presence of contrast differences between the stimuli and not reliably observed for categorically different hues equated in contrast; 2) there is no reliable difference between green- and blue-related difference waves in speakers (Russian) with two basic blue color categories, the difference waves, again, being driven by contrast rather than their categorical content. Our findings are highly significant for the debate concerning the interface between perception and cognition, as the absence of early categorical effects speaks against models that predict Whorfian-type preattentive cognitive influences on perception.